Ende Culture in East Nusa Tenggara: Unraveling the Rich Heritage and Traditions of an Enigmatic Region - Putu Herry Hermawan Priantara (Bali Tourism Journal, 2023)
The Lio inhabit the Ende Regency's eastern to northern regions. There is a village still occupied by the Lio tribe, namely Nggela Village. Located about 72 km from the city center of Ende, the Nggela Village Settlement is included in the traditional village in Wolojita District, Ende Regency, Flores-NTT, which still maintains its culture and customs. The pattern of traditional settlements in the town of Nggela, Ende Regency, is always seen about the place of origin, namely Mount Lepembusu. Cosmological considerations maintain a balance between the two extreme points and their relation to settlements, namely ulu (head) and eko (downstream), and there is a puse (center) as the center of traditional accommodations. Ulu is connected to the sunrise or towards Mount Lepembusu, while eko is towards the sunset or opposite the mountain. As a traditional settlement that still adheres to cultural values maintained today, the center of conventional ceremonial activities is carried out on the Kanga Ria / traditional Mesbah, in the middle of this traditional settlement. The traditional territory of Nggela Village is only inhabited by people with important positions and roles in society or commonly referred to as Mosalaki/traditional stakeholders, with a total of 17 people occupying 15 traditional houses. The behavior of the Nggela village community is strongly influenced by various conventional practices such as Loka Lolo, Joka Ju, and Lobo Keda. This ritual will determine how attitudes, emotions, values, ethics, power, persuasion, and genetics and assess the availability of space in Nggela village.